CT-guided biopsy of subdiaphragmatic small renal nodule with the coaxial technique using MPR images - Saba, Luca; Saba, Francesco; Fellini, Federica (Acta Biomedica Atenei Parmensis, 2019)
Summary. Purpose: To demonstrate the advantages of CT-guided biopsy of subdiaphragmatic small renal nodule with the coaxial technique using MPR images. Methods: The study included retrospectively 12 patients who underwent CT-guided biopsy with 18 G needle of subdiaphragmatic small renal nodule (<15 mm) suspected. Histology reports have been the reference standard. Results: The histology was diagnostic in 12 biopsies (100%): out of 10 neoplastic nodule (83.3%), 8 were malignant (80%) and 2 were benign (20%); 2 out of 12 were non-neoplastic (16.6%). No procedural complications were observed (0%). Conclusions: By using MPR images there is an effective improvement during coaxial CT-guided biopsy of subdiaphragmatic small renal nodule difficult to reach and to reduce the complication as pneumothorax. (www.actabiomedica.it)